Ověření skutečných fyzikálně-mechanických parametrů kompozitního materiálu - Jablonská, Markéta (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Diplomová práce řeší kompozitní materiály, detailněji se věnuje drátkobetonům. Práce je zaměřena na ověření mechanických vlastností drátkobetonu a to především jeho pevnosti v tahu za ohybu. Zkoušení bylo prováděno na betonech různých pevností s přidáním 30 kg na m3 ocelových drátků KrampeHarex DE 50/1,0 N. Práce obsahuje teoretickou a experimentální část.

Diploma thesis deals with composite materiál and it is dedicated to steel fiber concreat. The thesis focuses on verification of mechanical parameters of the steel fiber concrete. Especially on the compressive (tensile) strength at first cracking and the compressive strength in cracked state. Testing was conducted on concrete different tensile with 30 kg on m3 steel fibers KrampeHarex DE 50/1,0 N. The thesis is divided into theoretical and experimental part.
Verification of actual physical-mechanical parameters of composite material
Keywords: Kompozitní materiál; mechanické parametry; vláknobeton; drátkobeton; matrice; ocelová vlákna; zkoušky drátkobetonu; Composite material; mechanical parameters; fiber concrete; steel fiber concrete; matrix; steel fibers; tests steel fiber concrete